Ex-Parte Orders: Extent Of Duty Of Disclosure & Consequences Of The Breach - Sethu, R.R. (Journal of Malaysian and Comparative Law, 2019)
There is, in the administration of our system of justice, a procedure that enables one party to seek relief, usually temporary relief, ex parte. There are special rules governing this procedure. The most important aspect of this procedure is the duty to disclose all material facts failing wich the order is discharged. This judge-made rule, established in the last century, has shown some sign of reform: a movement away from the indiscriminate and rigid enforcement of the rule in all cases of non-disclosure. The purpose of this article is to examine the rule, its content, the consequences of its breach in its orthodox setting and the impact of the new-found indulgence on the rule. Though this indulgence emanated from England, as did the rule itself, there does not seem to be any reported Malaysian case where the new indulgence had been invoked or applied.